How Fast Tobacco Can Be: The Logistical Process at Rothmans of Pall Mall Indonesia in the 1997 Indonesian Economic Crisis - Heijden, R.J.E. van der; Wagner, B.G.; Sukoharsono, E. G. (The International Journal of Accounting and Business Society, 2004)
Every year Rothmans International Group publishes a geographical business report.  In  this  report  the  different  Asian  geographical  regions  are compared  with  one  another  concerning  profit,  costs,  sales  etc.  Before 1996, Rothmans of Pall Mall Indonesia was always at the 1st place concerning profit. This is because of the low costs spent in Indonesia.  In 1996 profits were declining and their place at the hit list was taken by Malaysia. This wakened the management in Jakarta and Malang. The Profit numbers were still declining due the higher costs than expected (sales maintain constant). The costs increased in the year of 1996 with 10% (usually between 4% and 6%). Those 10% total for a RP 2,6 billion:  1996.